Two women posing in a bar - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women posing in a bar. The woman on the right is seated sideways in a chair at the bar. Her left arm is resting on the back of the chair and her forehead is resting against the second womans cheek. The woman on the left is standing and leaning slightly toward the first woman. Her right hand is on the chair back also. The bar, a pack of cigarettes, bottles of alcohol, and a cash register are visible in the background.